Same Frame, New Picture: Changing Gender, Ethnic and Cultural Representation in Hollywood Genre Cinema - HARDIMAN, NEASA (Trinity College Dublin. School of Creative Arts. Discipline of Drama, 2019)
This study explores the potential of a Hollywood genre film to disestablish those retrogressive gender, ethnic and cultural representations that are frequently encoded in the tropes of Hollywood genre cinema. To that end, the study engages in a close analysis of six Hollywood genre films released between 2000 and 2015. These films are identifiably genre works that nonetheless appear to reconfigure key structuring tropes of their genre. The analysis gives rise to a set of strategies toward the creation of a cinema that offers the pleasures of the Hollywood genre film form, while tending to resist such retrogressive gender, ethnic and cultural representations as are typically encoded within that form. This set of strategies then informs an original screenplay, presented as an Appendix to this work. The six films under discussion are selected from the Hollywood genre oeuvre of three directors: Kathryn Bigelow, Jane Campion and Ang Lee. Each film is rooted in a recognizable genre idiom or combination of genre idioms. Divided into six chapters, the study focuses on one film per chapter, beginning with an overview of the film's generic provenance. Establishing the dominant contemporary conventions and tropes of that genre, each film is then examined as it reproduces, recodes or otherwise reframes those conventions by focussing on the film's three constitutive elements: its construction of protagonist, its presentation of gender and ethnic relations, and its expression of cultural context. The study reveals that all six films deploy a specific set of strategies in their engagement with genre idiom. All six begin by signalling, through their three constitutive elements, an adherence to familiar genre tropes, prompting clear genre recognition. The films then reconfigure, recode or otherwise reframe selected tropes of their genre to produce challenging, counter-generic meanings that disestablish certain conventions of representation, while remaining within the idiom of their chosen genre. However, the study concludes that the recoding of certain genre-typical thematic polarities can serve to disestablish one form of hegemonic representation, while effectively reproducing another form, a strategy that results in partial disruption and partial reinforcement of retrogressive genre norms. Informed by the set of strategies thus established, the original screenplay Sea Fever is presented as an Appendix to this work.
APPROVED
Keywords: Genre; Film